Preparation And Characterization Of Epoxy Particlefilled Thermosetting Composites - Low, Lay Foon (2012)

(untitled)
Water-based emulsion technique was used in this study to produce hollow epoxy particles (HEP) and solid epoxy particles (SEP). The HEP and SEP fillers were then chemically treated with hydrochloric acid solution to get rid of the excessive calcium carbonate on the surfaces of the fillers. It was found that HEP and SEP fillers could be optimally prepared at the homogenizing time of 9 minutes and 7 minutes, respectively under the homogenizing speed of 15,000 rpm. HEP fillers were added into the epoxy, vinyl ester and polyester thermosetting matrices at different loading amounts (0-9 wt%) to strengthen and toughen the thermosetting matrices.